Anthracene‐Fused Oligo‐BODIPYs: A New Class of π‐Extended NIR‐Absorbing Materials. Issue 5 (8th December 2022) - Labella, Jorge; Durán‐Sampedro, Gonzalo; Krishna, Swathi; Martínez‐Díaz, M. Victoria; Guldi, Dirk M.; Torres, Tomás
Abstract: Large π‐conjugated systems are key in the area of molecular materials. Herein, we prepare via Au I ‐catalyzed cyclization a series of fully π‐conjugated anthracene‐fused oligo‐BODIPYs. Their structural and optoelectronic properties were studied by several techniques, ranging from X‐ray, UV/Vis, and cyclic voltammetry to transient absorption spectroscopy. As a complement, their electronic structures were explored by means of Density Functional Theory (DFT) calculations. Depending on the size and shape of the π‐conjugated skeleton, unique features—such as face‐to‐face supramolecular organization, NIR absorption and fluorescence as well as strong electron accepting character—were noted. All in all, the aforementioned features render them valuable for technological applications. Abstract : Au I ‐catalyzed cyclization has been used to prepare a series of fully π‐conjugated anthracene‐fused oligo‐BODIPYs. The size and shape of the π‐conjugated skeleton determines the unique features of the compounds—such as their face‐to‐face supramolecular organization, NIR absorption and fluorescence as well as strong electron accepting character.